Atlas of multilineage stem cell differentiation reveals TMEM88 as a developmental regulator of blood pressure - Sophie Shen; Tessa Werner; Samuel W. Lukowski; Stacey Andersen; Yuliangzi Sun; Woo Jun Shim; Dalia Mizikovsky; Sakurako Kobayashi; Jennifer Outhwaite; Han Sheng Chiu; Xiaoli Chen; Gavin Chapman; et al. (Nature Communications)
Abstract Pluripotent stem cells provide a scalable approach to analyse molecular regulation of cell differentiation across developmental lineages. Here, we engineer barcoded induced pluripotent stem cells to generate an atlas of multilineage differentiation from pluripotency, encompassing an eight-day time course with modulation of WNT, BMP, and VEGF signalling pathways. Annotation of in vitro cell types with reference to in vivo development reveals diverse mesendoderm lineage cell types including lateral plate and paraxial mesoderm, neural crest, and primitive gut. Interrogation of temporal and signalling-specific gene expression in this atlas, evaluated against cell type-specific gene expression in human complex trait data highlights the WNT-inhibitor gene TMEM88 as a regulator of mesendodermal lineages influencing cardiovascular and anthropometric traits. Genetic TMEM88 loss of function models show impaired differentiation of endodermal and mesodermal derivatives in vitro and dysregulated arterial blood pressure in vivo. Together, this study provides an atlas of multilineage stem cell differentiation and analysis pipelines to dissect genetic determinants of mammalian developmental physiology.